Closed-loop spray drying with N2 of Moringa oleifera leaf ethanolic extracts: Effects on bioactive compounds and antiradical activity. Issue 14 (30th September 2021) - Vázquez-León, L. A.; Olguín-Rojas, J. A.; Páramo-Calderón, D. E.; Barbero, Gerardo F.; Salgado-Cervantes, M. A.; Palma, Miguel; García-Alvarado, M. A.; Rodríguez-Jimenes, G. C.
Abstract: Dried moringa ( Moringa oleifera ) extract was obtained by solid–liquid extraction from moringa fresh leaves with an ethanolic solution (80%) followed by closed-loop spray drying with N2 . This approach avoided the risk of explosion and environmental pollution upon drying. Spray drying was carried out with different inlet-outlet temperatures. Maltodextrin DE-10, β -cyclodextrin and precipitated silica were used as carrier materials. The highest statistically validated ( p  < 0.05) retentions (93% total phenolics and 48% ascorbic acid, 71% DPPH and 92% ABTS) were obtained with maltodextrin DE-10. The highest retentions of total carotenoids (72%) were obtained with precipitated silica. GRAPHICAL ABSTRACT: